ДВЕНАДЦАТИМЕСЯЧНЫЕ РЕЗУЛЬТАТЫ ЧКВ С ИСПОЛЬЗОВАНИЕМ СИРОЛИМУС И ЭВЕРОЛИМУС ПОКРЫТЫХ СТЕНТОВ - Р. С. Поляков; С. А. Абугов; Г. В. Марданян; Ю. М. Саакян; М. В. Пурецкий; А. А. Пиркова; А. В. Болтенков; С. М. Наумов («REMEDIUM GROUP» Ltd., 2013)
.